2021
DOI: 10.1007/s00382-021-06076-1
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal forecast barrier of the North Atlantic oscillation in S2S models during the extreme mei-yu rainfall event in 2020

Abstract: Enhanced predictability of high-impact weather events is a Subseasonal to Seasonal Prediction Project (S2S) priority. In early summer 2020, a record-breaking heavy rainfall event occurred over the Yangtze River valley during the mei-yu season (June and July). Here we evaluate the S2S model forecast performance concerning the summer 2020 extreme mei-yu event over the Yangtze River valley. Our results show all operational S2S models exhibit fluctuating high-low-high forecast skill patterns during this three-stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Associated detection results and intercomparisons are displayed in the time‐longitude diagrams (Figure 5) and spatial distributions (Figure 6). As reported previously, the record‐breaking Meiyu‐related extreme precipitation events occurred over MLRYR in June and July 2020 (Yan et al, 2022; Zheng & Wang, 2021; Zhou et al, 2021), characterized by an advanced onset, long‐term persistence and delated retreat (Ding et al, 2021; Qiao et al, 2021). Regarding process evolutions, the 2020 MLRYR extreme precipitations are caused by two‐stage front‐related heavy rainfalls.…”
Section: Case‐based Validation Of Typical Extreme Eventsmentioning
confidence: 56%
“…Associated detection results and intercomparisons are displayed in the time‐longitude diagrams (Figure 5) and spatial distributions (Figure 6). As reported previously, the record‐breaking Meiyu‐related extreme precipitation events occurred over MLRYR in June and July 2020 (Yan et al, 2022; Zheng & Wang, 2021; Zhou et al, 2021), characterized by an advanced onset, long‐term persistence and delated retreat (Ding et al, 2021; Qiao et al, 2021). Regarding process evolutions, the 2020 MLRYR extreme precipitations are caused by two‐stage front‐related heavy rainfalls.…”
Section: Case‐based Validation Of Typical Extreme Eventsmentioning
confidence: 56%
“…Tropical variability provides the major source of subseasonal predictability. Our previous studies have revealed that the subseasonal predictability of the East Asia summer monsoon in S2S models is driven by tropical variability but largely constrained by the poor skill of mid‐high latitude atmospheric variations (Liu et al., 2020; Yan et al., 2022). Generally, the S2S model forecast skills for weekly accumulated precipitation were low when the lead time was beyond 2 weeks in extratropical continental areas (de Andrade et al., 2019; Li & Robertson, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Domeisen et al (2022) analyzed the advances in S2S probabilistic forecasts of several extreme rainfall events and illustrated the potential for event-dependent advance warnings. However, the S2S models show distinct forecast skills and effective lead times for individual heavy rainfall events, depending on the broad-scale atmospheric conditions and oceanic signals (e.g., Cowan et al, 2019;Doss-Gollin et al, 2018;Yan et al, 2022).…”
mentioning
confidence: 99%
“…Numerous studies have identified the importance of extratropical intraseasonal oscillations along the SJ (EISO-SJ) on causing regional subseasonal variations and frequently triggering extreme meteorological events, such as heatwaves (Schubert et al 2011, Gao et al 2018 and flooding (Dugam et al 2009, Li et al 2021. Meanwhile, EISO-SJ has been proven to significantly affect the local subseasonal prediction skills (Qi and Yang 2019, Liu et al 2020, Yan et al 2021, 2022 and even provides a window of opportunity for East Asian subseasonal prediction (Zhu et al 2023). Therefore, understanding the factors affecting the variations and features of EISO-SJ is crucial for the subseasonal community.…”
Section: Introductionmentioning
confidence: 99%